Effects of nitrogen deposition on water use efficiency of global terrestrial ecosystems simulated using the IBIS model. (June 2019) - Lu, Xuehe; Ju, Weimin; Jiang, Hong; Zhang, Xiuying; Liu, Jinxun; Sherba, Jason; Wang, Songhan
Highlights: The effects of N deposition on global WUE were evaluated with IBIS model. WUE changed in several N deposition hotspots owing to larger change in GPP than in ET. N deposition has significantly increased the response ratio of WUE to elevated CO2 in some regions. Abstract: Nitrogen (N) deposition changes the availability of N in ecosystems and regulates carbon and water cycles, including ecosystem water use efficiency (WUE). In recent decades, N deposition has been increasing rapidly, especially at several hotspots in China, Europe and the U.S. In this study, a process-based terrestrial ecosystem model, IBIS (Integrated BIosphere Simulator), was used to simulate the effects of N deposition on WUE globally. The results indicated that increasing N deposition led to a global increase in WUE of 0.005 g C kg −1 H2 O on average over the first 10 years of the 21st century. The effects of N deposition on WUE were more evident in certain hotspots than in other parts of the world. The effect of N deposition on gross primary productivity (GPP) determined the change in WUE. In particular, high N deposition led to decreased ET and consequently increased the WUE in southeastern China. Moreover, increased N deposition has significantly enhanced the WUE in response to elevated CO2 in southeastern China, indicating the importance of N deposition in regulating the terrestrial carbon cycle.